2022
DOI: 10.1101/2022.01.11.475791
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparable human spatial memory distortions in physical, desktop virtual and immersive virtual environments

Abstract: Boundaries define regions of space and are integral to episodic memories. The impact of boundaries on spatial memory and neural representations of space has been extensively studied in freely-moving rodents. But less is known in humans and many prior studies have employed desktop virtual reality (VR) which lacks the body-based self-motion cues of the physical world, diminishing the potentially strong input from path integration to spatial memory. We replicated a desktop-VR study testing the impact of boundarie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…Nonetheless, the resulting set of 63 videos will provide a reliable resource for future empirical studies of architectural experience, confirmed by the aforementioned results replicating findings previously attributed to still images (Coburn et al, 2020). As argued in section 1, emotion is central to the study of architectural experience (Mallgrave, 2013;Zisch, Gage and Spiers, 2014), so it was particularly important that the videos in the dataset resulted in consistently positive or negative valence ratings across participants.…”
Section: Validating a Novel Dataset Of Valenced Videossupporting
confidence: 77%
See 4 more Smart Citations
“…Nonetheless, the resulting set of 63 videos will provide a reliable resource for future empirical studies of architectural experience, confirmed by the aforementioned results replicating findings previously attributed to still images (Coburn et al, 2020). As argued in section 1, emotion is central to the study of architectural experience (Mallgrave, 2013;Zisch, Gage and Spiers, 2014), so it was particularly important that the videos in the dataset resulted in consistently positive or negative valence ratings across participants.…”
Section: Validating a Novel Dataset Of Valenced Videossupporting
confidence: 77%
“…Future work could address this by creating bespoke videos and possibly through the use of 360 degree film footage with sound presented via immersive virtual reality (VR) (Mazumder, Spiers & Ellard, 2020). Another approach would be to use laser-scanning of environments for porting in VR and then manipulating the architecture in the models (Zisch et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations